Economic Spectrofluorometric Bioanalysis of Empagliflozin in Rats’ Plasma - Bassam Ayoub; Noha El Zahar; Haidy Michel; Mariam Tadros (Journal of Analytical Methods in Chemistry)
A simple, economic, green, and sensitive bioanalytical method for empagliflozin bioassay in rats’ plasma was employed successfully owing to the empagliflozin native fluorescence behavior. Enhanced liquid-liquid extraction, using diethyl ether (DEE), was successfully employed for the improved extraction of empagliflozin from rats’ plasma based on its high value of logP as 1.8 that boosted the drug migration from plasma to the organic layer. The relative fluorescence intensity for empagliflozin was recorded at emission (299.4 nm) after excitation at 226.5 nm. The method was validated with satisfactory results for linearity (500–5000 ng/mL), trueness, precision, the matrix effect, and extraction recovery. The matrix effect ranged between 15.63% and 23.10% for LQC and HQC samples, respectively. Extraction recovery ranged between 54.61% and 62.54% for LQC and HQC samples, respectively. Bias values for the trueness ranged between −10.62 and +14.95, while %RSD values for the precision ranged between 5.39% and 9.33%. The method was successfully applied to rats’ plasma samples that included six rats, and the drug concentration was determined in their plasma after 1 hour (estimated Cmax based on literature) following oral administration of empagliflozin with a concentration of 10 mg/Kg, p.o.. The developed cost-effective spectrofluorimetric method in the present work will be of beneficial use in further pharmacokinetic studies that include rats’ plasma and biological fluids. Moreover, with the suitable modifications, the described novel extraction of empagliflozin could be adopted to human plasma samples and future clinical studies. Moreover, development of new simple cost-effective methods is necessary to give the researchers a set of “varieties” that they can use according to the laboratory limitations, especially in the developing countries in addition of being a greener method due to the lower consumption of toxic solvents and lower waste production.